Combined chemoradiation of cisplatin versus carboplatin in cervical carcinoma: A single institution experience from Thailand - Ekkasit Tharavichitkul (2018)
© 2016 The Author(s). Background: To report the results of combined chemoradiation (CCRT) with cisplatin versus carboplatin in locally advanced cervical carcinoma. Methods: From 2009 to 2013, 255 patients with stage IIB-IVA cervical carcinoma, according to FIGO staging were prospectively assigned to be treated with pelvic radiotherapy followed by brachytherapy given concurrently with cisplatin or carboplatin in the treatment of locally advanced cervical cancer. Treatment outcomes and toxicitiy were evaluated. Results: Two-hundred and thirteen patients could be evaluated. At a median follow-up time of 43 months (6-69 months), the 3-year local control, disease-free survival, metastasis-free survival and overall survival rates were 93, 80.8, 85.0 and 87.3 %, respectively. No statistical difference in terms of local control, disease-free survival, metastasis-free survival and overall survival rates between cisplatin and carboplatin treatments was observed in this study. Eighty-six percents of the patients in the carboplatin group could receive more than 4 cycles, while there were only 72 % in the cisplatin group who completed more than 4 cycles (p = 0. 02). In terms of acute toxicity, cisplatin caused significantly more anemia (p = 0.026), neutropenia (p = 0. 044) and nephrotoxicity (p = 0. 031) than carboplatin. No difference in late toxicity was observed in this study. Conclusion: Carboplatin yielded comparable results to cisplatin in concurrent chemo-radiation for locally advanced cervical cancer. In addition, carboplatin was associated with a better compliance rate and was associated with less of anemia, neutropenia and nephrotoxicity.